Three new species of Neoperla in the montivaga group (Plecoptera: Perlidae) from China - Kong, Fanbin; Lv, Junfeng; Li, Weihai (Zootaxa, 2014)
Three new species of the genus Neoperla in the montivaga species group, N. baisha Kong & Li, sp. nov., N. bicurvata Kong & Li, sp. nov., and N. furcomaculata Kong & Li, sp. nov., are proposed from Hainan Province, China. Their taxonomic relationships are discussed with related congeners.